ANALISIS MANFAAT INVESTASI TEKNOLOGI INFORMASI PADA PT BANK MAYBANK INDONESIA TBK - Ni Kadek Bintang Novita Dwinantari; I Gst. Agung Pramesti Dwi Putri; Putri Anugrah Cahya Dewi (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
This research aims to analyze the benefits of information technology investment at PT Bank Maybank Indonesia Tbk by using two research methods, namely Rantis's Generic IS/TI Business Value and Cost Benefit Analysis. The use of the Cost Benefit Analysis method is used to analyze the feasibility of a technology investment by identifying the costs incurred and the benefits obtained. Ranti's Generic IS/TI Business Value method is used to identify the benefits obtained from a technology investment. The results obtained by using the cost benefit analysis calculation show that the information technology investment made by PT Bank Maybank Indonesia Tbk is acceptable and provides benefits for the company by obtaining an ROI of 0.72%, an NPV of 2,607,198, a PP of 0.06 or around 22 days, and a BCR of 55.9. While the results of the analysis of the benefits of information technology investment using the Ranti's Generic IS/IT Business Value method provide benefits in the form of improving image, improving external services, improving internal services, and improving quality.